2013
DOI: 10.1177/1040638713476865
|View full text |Cite
|
Sign up to set email alerts
|

Fin and gill biopsies are effective nonlethal samples for detection of Viral hemorrhagic septicemia virus genotype IVb

Abstract: Nonlethal sampling is becoming a common method to diagnose fish diseases, especially with the availability of molecular testing. Viral hemorrhagic septicemia virus (VHSV) is a viral pathogen of finfish distributed worldwide. Although VHSV has been known to occur in some parts of the world for decades, a new genotype, IVb, recently emerged in the Laurentian Great Lakes of northeastern North America. Golden shiners (Notemigonus crysoleucas; Mitchill, 1814) and fathead minnows (Pimephales promelas; Rafinesque, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Gills have in various species proven to be a good organ for detecting VHSV carrying fish [28], [43], [46]. The results obtained by Cornwell et al [46] further indicate that the sensitivity of detecting VHSV in gill samples might vary between species. The ability of VHSV to infect the gills has also been correlated to virulence [47].…”
Section: Discussionmentioning
confidence: 99%
“…Gills have in various species proven to be a good organ for detecting VHSV carrying fish [28], [43], [46]. The results obtained by Cornwell et al [46] further indicate that the sensitivity of detecting VHSV in gill samples might vary between species. The ability of VHSV to infect the gills has also been correlated to virulence [47].…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate this potential bias, several replicate samples would be required over a period where the virus state of the species within the site did not change. Such a design would require a non-lethal sampling technique (Cornwell et al, 2013) that was not available during the time this study took place. Additionally, the cross sectional design of this study did not allow estimation of incidence and it is possible that seasonal changes in virus prevalence, such as the long-term changes documented by Eckerlin et al (2011) may have an effect on the reported prevalence estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The recent single survey occupancy estimation procedure developed by Lele et al (2012) holds particular promise. Additionally, the non-lethal sampling described by Cornwell et al (2013) would enable the ability to have several replicate visits to a site in the form of repeated measures in order to estimate site occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured populations of these species were available that underwent annual fish health inspections (American Fisheries Society 2010) and had been consistently found to be free of VHSV as well as other important fish pathogens. Cornwell et al (2013) demonstrated VHSV-infected Fathead Minnow fin or gill samples tested alone by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) were equally as sensitive as a pooled organ-sample cultured for viral detection. Their results suggested that nonlethal fin or gill biopsies can be used to study the infection dynamics of VHSV IVb in fish.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%